2014
DOI: 10.1590/0104-4060.36544
|View full text |Cite
|
Sign up to set email alerts
|

"Prendam suas bezerras que o meu garrote está solto!" Interseccionando gênero, sexualidade e lugar nos modos de subjetivação regionais

Abstract: This paper analyses aspects of the discursive production of heteronormativity at a regional intersection. Inspired by post-critical perspectives, we assume discursive-deconstructionist problematizations about prescriptive or contesting sexual experimentations and forms of regulation, of normalization or of gender contestation. We try to understand how the body constitutes itself as a discursive materiality of practices and of heteronormative regulation manners, also considering this process on compulsory heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
2
Order By: Relevance
“…In Table 6 you can see the frequency of articles by type of effect. It can be observed that in the researched literature, the results are statis tically significant in 60.87% of production, totaling 14 articles (SEFFNER, 2011;WENETZ, 2012;RABELO, 2013;ALTMAN;AYOUB;AMARAL, 2011;DORNELLES;POCAHY, 2014;PINTO, 2011;TORRES;PRADO, 2014;ROCHA, 2012;XAVIER FILHA, 2012;SOARES, 2014;ALONSO;ZURBRIGGEN, 2014;EHRENBERG, 2014;DORNELLES, 2012;MOIZÉS;BUENO, 2010). In this perspective, the status of more than 60% of the produced literature on the subject suggests that the approach of the themes of body, gender and sexuality in teacher education contributes to the destabilization of norms, classifications and hierarchies surrounding the subject.…”
Section: The Development Of the Meta-analysismentioning
confidence: 97%
See 1 more Smart Citation
“…In Table 6 you can see the frequency of articles by type of effect. It can be observed that in the researched literature, the results are statis tically significant in 60.87% of production, totaling 14 articles (SEFFNER, 2011;WENETZ, 2012;RABELO, 2013;ALTMAN;AYOUB;AMARAL, 2011;DORNELLES;POCAHY, 2014;PINTO, 2011;TORRES;PRADO, 2014;ROCHA, 2012;XAVIER FILHA, 2012;SOARES, 2014;ALONSO;ZURBRIGGEN, 2014;EHRENBERG, 2014;DORNELLES, 2012;MOIZÉS;BUENO, 2010). In this perspective, the status of more than 60% of the produced literature on the subject suggests that the approach of the themes of body, gender and sexuality in teacher education contributes to the destabilization of norms, classifications and hierarchies surrounding the subject.…”
Section: The Development Of the Meta-analysismentioning
confidence: 97%
“…Researchaction and workshops were used in two studies each (8.69%), respectively in the studies: Xavier Filha (2012); Moizés and Bueno (2010); Pinto (2011); Silva and Soares (2014). Finally, the focus group and the field report were used as qualitative technique in one (4.34%) study each: Dornelles and Pocahy (2014) and Ferrari and Almeida (2012).…”
Section: The Development Of the Meta-analysismentioning
confidence: 99%
“…O currículo é um espaço de embates de políticas culturais, portanto, é vinculado às relações de poder, não apenas no plano estatal, mas espalhadas em toda a rede social, que inclui em seu mapa os processos de dominação centrados na raça, etnia, classe, no gênero e na sexualidade (SILVA, 2011). As questões do corpo, gênero e sexualidade, silenciadas ou normatizadas na prática pedagógica, aparecem de modo imprevisto na sala de aula (DIAS, 2015a;SEFFNER, 2011;DORNELLES;POCAHY, 2014;PINTO, 2011). Tendo em vista que o currículo escolar não é neutro e que as questões de gênero e sexualidade estão nele presentes, implícita e explicitamente, as políticas e práticas curriculares podem reforçar ou questionar as desigualdades, normatizações, estereótipos, preconceitos e discriminações concernentes à sexualidade e ao gênero (DIAS, 2014b).…”
Section: Gênero E Sexualidade No Currículo Escolarunclassified
“…For the authors, "the status of more than 60% of the produced literature on the subject suggests that the approach of the themes of body, gender, and sexuality in teacher education contributes to the destabilization of norms, classifications and hierarchies surrounding the subject. This result is very significant, because it is an analysis of the specific area of knowledge production, highlighting the studies as relevant (SEFFNER, 2011;WENETZ, 2012;RABELO, 2013;ALTMAN;AYOUB;AMARAL, 2011;POCAHY, 2014;PINTO, 2011;PRADO, 2014;QUIRINO;ROCHA, 2012;XAVIER FILHA, 2012;SOARES, 2014;ALONSO;ZURBRIGGEN, 2014;EHRENBERG, 2014;DORNELLES, 2012;MOIZÉS;BUENO, 2010;SANTOS, 2020;CRUZ, 2014;MENEZES, 2017;DIAS, 2017;DIAS, 2014;EUGÊNIO, 2010;GOMES-DA-SILVA, 2014, LARA, 2016CALEJON, 2020).…”
Section: Introductionmentioning
confidence: 95%